Adaptasi individual dan kolektif: Respons masyarakat Indonesia menghadapi pandemi COVID-19 - Wenty Marina Minza; Faturochman Faturochman; Syurawasti Muhiddin; Wahyu Jati Anggoro (Jurnal Psikologi Sosial, 2022)
The COVID-19 pandemic has given an impact on various aspects of human life forcing humans to adapt to the existing condition. This study aimed to explore the adaptation process toward the COVID-19 pandemic in Indonesia. The research method applied was quantitative-descriptive. A total of 544 Indonesian citizens filled out an online social perception toward risk and spread of COVID-19 scale through a google form. The results focused on the adaptive response of the community consisting of both perceptions and behaviors. This study found that the adaptation of the society to deal with COVID-19 did not only occur at the individual level but also at the collective level. At the individual level, there were two kinds of psychological adaptation found namely active and passive. At the collective level, this study suggested that collective coping is an important form of social-psychological adaptation in which solidarity is the essence of the process.